Features of the Introduction in Schools of Nonverbal Communication Development Programme for Children with Intellectual Disabilities - Zashchirinskaia, Oksana V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The present study was conducted to identify the features of nonverbal communication in children. Background: Nonverbal communication is a significant aspect of interpersonal communication. American scientists have found a strong correlation between low ability to recognise facial expressions, interpretation of postures, and gestures with communication difficulties. Experimental data indicate a positive relationship between the social status of an individual and the ability to interpret nonverbal signals. The general dynamics of the development of a child with disabilities are subject to the same laws as ordinary children. But the peculiarities of children associated with a disturbance of the intellectual sphere lead to the limitation of possibilities to obtain information from the outside world, a change in the methods of communication, difficulties of social adaptation, and impoverishment of social experience. Method: Students of the first-grades of educational institutions of St. Petersburg were the survey sample. Several public and special schools were randomly selected in order to form the most detailed picture of the development of nonverbal behaviour in children, as well as to obtain the most representative sample for our study. A total of 128 children took part in the study – students of the first-grade (average age – 7.4 years; 47 girls, 81 boys). Results: A programme of psychological influence was developed to optimise the nonverbal communication of children with intellectual disabilities. Conclusion: With psychological influence aimed at the development of nonverbal communication among primary schoolers with intellectual disabilities, more intact mental functions associated with the implementation of emotional and behavioural components were taken into account.